Elevated level of lecithin:cholesterol acyltransferase (LCAT) is associated with reduced coronary atheroma burden. (September 2018) - Gebhard, Catherine; Rhainds, David; He, Gang; Rodés-Cabau, Josep; Lavi, Shahar; Spence, J. David; Title, Lawrence; Kouz, Simon; L'Allier, Philippe L.; Grégoire, Jean; Ibrahim, Reda; Cossette, Mariève; et al.
Abstract: Background and aims: Lecithin:cholesterol acyltransferase (LCAT), a key enzyme in high-density lipoprotein (HDL) metabolism and reverse cholesterol transport (RCT), has been associated with atheroprotection. However, its relation to plaque characteristics has not been confirmed to date. We aimed to determine the relationship between plasma LCAT mass concentration and plaque burden in a multi-center imaging study. Methods: Two hundred sixty-seven patients with angiographically proven coronary artery disease (CAD) underwent intravascular ultrasonography (IVUS) imaging. Ninety-six patients without CAD served as controls for biochemistry assessments. Results: Plasma LCAT mass concentration was higher in CAD patients as compared to controls (8.94 ± 2.51 μg/mL vs. 7.89 ± 2.99 μg/mL, p  = 0.003), while cholesterol esterification rate (CER) was downregulated (253.6 ± 83.9 μM/2 h vs. 315.3 ± 115.0 μM/2 h, p <0.0001). Both parameters correlated inversely with total atheroma volume (r = −0.14, p  = 0.027 and r = −0.14, p  = 0.024, respectively), while only LCAT mass was found to be a significant predictor of atheroma volume (β-coefficient −0.18, p  = 0.0047) when tested in a stepwise linear regression model against known CAD risk factors as predictor variables. Accordingly, patients with LCAT mass in the highest quartile had significantly less atheroma burden than those in the lower quartiles (39.7 ± 10.7% vs. 45.4 ± 10.4%, p  = 0.0014 for highest vs. lowest quartile of LCAT mass). Conclusions: Plasma LCAT mass concentration is upregulated in CAD patients and inversely related to plaque volume, suggesting atheroprotective effects. LCAT mass concentration outperformed LCAT activity in risk prediction models for atheroma burden, suggesting that LCAT mass is a key variable in atheroprotection. Further studies assessing LCAT as a therapeutic target in cardiovascular disease are warranted. Highlights: Loss-of-function LCAT mutations invariably result in profound HDL deficiency. The effect of LCAT on atherogenesis remains poorly understood. We demonstrate that plasma LCAT protein concentration is higher in patients with CAD as compared to controls. In these patients, LCAT correlates inversely with coronary atheroma burden. Our data suggest that LCAT exerts atheroprotective functions in CAD patients. Targeting LCAT in patients might be a promising therapeutic strategy to reduce cardiovascular risk.